Influence of the leader in the processes of management school, and paintings in their steps fractals (2014)
ABSTRACT: The objective of this research is to identify the characteristics of the leaders in the processes of school management, leadership styles, skills of the leader, also discusses the responsibilities in leadership, all of this applied to the area of school management. The analysis allowed identifying the action of the leadership, defining the responsibility of the leadership school, focusing on their functions and the development of skills for effective school leadership, all of this to achieve a management of academic quality.